Effect of Roasting Process on Antioxidant Activity of Carica Seeds Coffee (Carica pubescens) - Sukowati, Siski Andini; Arif, Zulhan; Heryanto, Rudi (Indonesian Scholar Society, 2022)
Carica seeds (Carica pubescens), one of the diversification of coffee drinks, served as antioxidants. The roasting process generated degradation of secondary metabolic compounds but produced Maillard reactions products (MRPs). The study aimed to determine the effect of the roasting process on the antioxidant activity of Carica coffee beans and its correlation to the Maillard reaction. The samples roasting temperatures were 100–115, 150–165, and 200–215 °C. The samples were analyzed for proximate, total phenolic, antioxidant, and FTIR. The moisture and ash content of dry seeds were according to SNI 01-2907-2008. The total phenolic content was 3.21–8.99 µgGAE/g, with the highest contents at 200–215 °C. The antioxidant activity was 83–459.67 ppm AEAC. The high phenolic content and antioxidant at 200–215 °C were thought to come from MRPs compounds. The FTIR spectra showed stretching of OH, C=C (aromatic), C=N, C=O, and C-OH (phenol). The spectrum intensity weakened at higher temperatures. However, only the nC–H stretching at 200–215 °C became stronger. The Cluster Ward analysis showed resemblance spectra at roasting temperature levels of 100–115 and 150–165 °C. The roasting process affected the antioxidant activity of Carica coffee beans, thereby increasing the roasting temperature level. This condition resulted in higher levels of antioxidants.